A combined GPS/Stated Choice experiment to estimate values of crash-risk reduction - Simon Fifer; Stephen Greaves; John Rose; Richard Ellison (Journal of Choice Modelling, 2011)
This paper details the development and application of a Stated Choice (SC) experiment designed to explore motorists sensitivities to a kilometre-based charging regime focused around crash-risk reduction. Responses are gathered through a SC experiment that pivots off actual driving behaviour collected over a five week period using an in-vehicle Global Positioning System (GPS) device. This provision of greater reality using revealed preference (RP) information ensures that the alternatives in the SC experiment are embedded in reality, providing motorists with a more realistic context for their choices. The study demonstrates with the improved affordability, power and consumer familiarity with GPS devices, the integration of GPS recorded travel information with SC experiments is a now a feasible solution which can help enrich the quality of the reference alternatives in SC experiments in the future.
Keywords: 330; stated choice; revealed preference GPS